Women’s Stories of Waste Picking in the City: “People Look at Us Like We Are Mad, but I Don’t Care” - Sibanda, Princess A.; Erwin, Kira (Social and Health Sciences)
The gendered dynamics of informal work in southern cities across the globe has been well documented. Women in the informal sector, usually already marginalised through racialised and class positionalities, face predictable work challenges in patriarchal society, lower pay, longer work hours, more family responsibilities, less social protections, and safety concerns linked to workspaces. In this article, we explore the specific challenges that women waste pickers in the inner city of Durban, South Africa, experience. The study draws on ethnographic research with eight waste pickers. Beyond the challenges, the narrative data illustrates how and why women waste pickers navigate and negotiate for space and safety in the inner city of Durban. We highlight how women build social relationships as a mitigation strategy against material and varied safety concerns. These social relationships work across formal business linkages and relationships on the street. These mitigation strategies are simultaneously gendered responses to work in the city and innovative business practices. The experiences of women waste pickers in the city indicates that it is left to the women themselves, individually and in small collectives, to find ways to navigate issues of discrimination and exclusions linked to work, gender and space in the city. Ultimately, we draw on the experiences of women waste pickers in inner city Durban to ask questions about what lessons can be learnt to advocate better municipal planning that proactively deals with gender and justice in the city.